Young adults' social drinking as explained by an augmented theory of planned behaviour: the roles of prototypes, willingness, and gender - Zimmermann, Friederike; Sieverding, Monika (British journal of health psychology, 2010)
This study focused on young adults' alcohol consumption in social contexts. A dual-process model (including reasoned action and social reaction) was applied by combining the theory of planned behaviour (TPB) and the prototype/willingness model. A key question was whether willingness and actor and abstainer prototype variables would augment the TPB by increasing explained variance.
Gesehen am 31.10.2023